Thrombophilic Polymorphisms Are Common in Women with Fetal Loss without Apparent Cause - Brenner, B.; Sarig, G.; Weiner, Z.; Younis, J.; Blumenfeld, Z.; Lanir, N. (Thrombosis and Haemostasis, 1999)
An association between fetal loss and thrombophilia has recently been described but has not been yet fully elucidated. We have evaluated prospectively the prevalence of the three common thrombophilic polymorphisms (TP) factor V G1691A (Leiden), thermolabile-methyl-enetetrahydrofolate reductase (TL-MTHFR) C677T and factor II G20210A mutations, in 76 women with fetal loss (≥3 in first, ≥2 in second, ≥1 in third trimester) without apparent cause and 106 controls without fetal loss. Thirty seven out of 76 (49%) of the women in the fetal loss group had at least one TP compared to only 23/106 (22%) in the control group (p = 0.0001). Factor V-Leiden was more common in the fetal loss group 24/76 (32%) compared to the control group 11/106 (10%) (OR = 4.0, 95% CI: 1.8-8.8, p <0.001). Five of the 76 patients (7%) were homozygous for factor V-Leiden compared to none of the controls (p = 0.012). A trend, albeit no statistically significant difference was found between women with fetal loss and control groups regarding factor II G20210A (8% vs. 4% respectively, OR = 2.2, 95% CI: 0.6-8.0, p = 0.23) and MTHFR C677T (18% vs. 10% respectively, OR = 1.95, 95% CI: 0.83-4.6, p = 0.12). Combined TP were documented in 6/76 (8%) patients compared to 1/106 (1%) in controls (OR = 9.0, 95% CI: 1.1-76, p = 0.02). Second or third trimester fetal loss were more common cause of pregnancy termination in 37 patients with TP compared to 39 patients without TP (57/158 (36%) vs. 23/135 (17%) respectively, (p = 0.0004). Thrombophilic polymorphisms are common in women with fetal loss without apparent cause and are associated with late pregnancy wastage. Combinations of TP increase the risk for fetal loss.